TIOCETAM IN COMPLEX THERAPY OF PLACENTAL INSUFFICIENCY - Simrock, V.V.; Cherkasova, V.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
A clinical inspection is conducted 53 pregnant with placental insufficiency. As a result Doppler ultra-sonography researches of fetus and placenta complex are exposed multiplying a sistolo-diastolic index in uterine arteries, arteries of umbilical cord and middle cerebral artery of fetus. Plugging of tiocetam in therapy of placental insufficiency for pregnant is instrumental in normalization of indexes of Doppler ultrasonography that in a clinical plan combines the improvedfetal condition and benefitial perinatal outcome.